Interaction of Cis- and Trans-RuCl (2)(DMSO)(4) With Human Serum Albumin - Trynda-Lemiesz, Lilianna (Hindawi Publishing Corporation, 2000)
The interaction between cis- and trans- RuCl(2)(DMSO)(4) and human serum albumin have been investigated through UV-Vis, circular dichroism, fluorescence spectroscopy and inductively couplet plasma atomic emission spectroscopy (ICP(AES)) method Albumin can specifically bind 1 mole of cis-isomer and 2 moles of the trans-isomer RuCl(2)(DMSO)(4) complex. The interaction of RuCl(2)(DMSO)(4) with HSA causes: a conformational change with the loss of helical stability of protein; the strong quenching of the Trp 214 fluorescence indicating that the conformational change of the hydrophobic binding pocked in subdomain IIA takes place; a local perturbation of the warfarin binding site and induce some conformational changes at neighbour domains, a changing of the binding abilities towards heme.